PERAN GURU GEOGRAFI DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X MERDEKA B SMA NEGERI 1 BIREUEN - Jannah, Rauzatul; A. Rahman, Aisyah; Muslihin (Bestari: Jurnal Pendidikan dan Kebudayaan, 2025)
This research aims to determine the role of geography teachers, the obstacles they face, and the solutions for improving students' learning motivation. This study employs a descriptive qualitative approach, with the research subjects including geography teachers as the primary respondents, while the school principal and students in class X Merdeka B are designated as supporting informants. Data was collected through observation, interviews, and document studies, and the validity of the data was tested for authenticity using source and technique triangulation. Subsequently, the data was analyzed through the stages of reduction, presentation, and conclusion drawing. The research findings confirm that geography teachers play an important role in motivating students, including by: (1) activating student participation through questions and answers about the material, (2) creating a conducive classroom environment, (3) utilizing various teaching methods and media, (4) providing rewards in the form of praise or grades, and (5) involving students in group work. The obstacle teachers face is the difference in students' ability to understand the lesson. As for the solution implemented by the teacher, it is through outdoor learning activities (field practice). Keywords: Role of Geography Teachers, Learning Motivation, Geography Learning